2012
DOI: 10.1136/bjophthalmol-2012-302167
|View full text |Cite
|
Sign up to set email alerts
|

Measuring the benefit of 4 years of intravitreal ranibizumab treatment for neovascular age-related macular degeneration

Abstract: We suggest that the numbers of patients with a particular level of vision may best reflect the actual benefit of AMD treatment provided by a service. Long-term follow-up is required as only 72/730 (10%) had been discharged at 36 months, half of whom had good vision of greater than 60 letters. 83% and 65% of patients needed treatment in the third and fourth year. Follow-up may be for the rest of the patients' life or at some point they may no longer be well enough to attend.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
30
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 12 publications
7
30
0
Order By: Relevance
“…Holz et al 13 also reported that 11.7% (n = 199) of their patients had both occult and classic lesions. Heimes et al 14 and Pushpoth et al 15 reported the combined number of patients with either predominantly or MC lesions. These two values could not be separated and were therefore excluded from the analysis of lesion type.…”
Section: Baseline Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Holz et al 13 also reported that 11.7% (n = 199) of their patients had both occult and classic lesions. Heimes et al 14 and Pushpoth et al 15 reported the combined number of patients with either predominantly or MC lesions. These two values could not be separated and were therefore excluded from the analysis of lesion type.…”
Section: Baseline Characteristicsmentioning
confidence: 99%
“…These two values could not be separated and were therefore excluded from the analysis of lesion type. Pushpoth et al, 15 Katz et al, 16 and Abedi et al 17 reported the combined number of patients with MC or occult lesions, and these were included into the occult category for analysis.…”
Section: Baseline Characteristicsmentioning
confidence: 99%
“…For example, patients with good baseline acuity demonstrated a smaller improvement in response to ranibizumab than patients with poor baseline acuity, 29,32 while treatmentnaive patients showed a better response than previously treated individuals. 26 Differences such as these may obscure the effects of treatment if the numbers of patients from a particular group are unrepresentative of the population as a whole. However, with nearly 20 000 patients analysed, the real-life data reviewed here could be considered as representative of current practice.…”
Section: Discussionmentioning
confidence: 99%
“…Mean VA at baseline ranged from 48.8 to 61.6 letters, excluding the studies by Shona et al, 32 Pushpoth et al, 26 and Nomura et al, 28 who reported VA outcomes for groups of patients stratified according to different …”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation